Luxembourg : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper considers features of the Luxembourg tax system that may be susceptible to changes in international tax transparency standards and surveys related policy options. Luxembourg's predictable and generally low-rate tax system has helped establish it as a leading financial and commercial entrepot and has supported its fiscal revenues. Its revenue base could, however, be susceptible to changes in the European Union and global tax environment. This paper highlights that to address potential challenges to Luxembourg's revenue base, the tax policy review should explore selective rate increases and base broadening measures. Moreover, the tax practices should seek to avoid encouraging unnecessary complexity in corporate ownership structures and intragroup financial contracts.